320 × 256 high operating temperature mid-infrared focal plane arrays based on type-II InAs/GaSb superlattice. (November 2017) - Sun, Yaoyao; Wang, Guowei; Han, Xi; Xiang, Wei; Jiang, Dongwei; Jiang, Zhi; Hao, Hongyue; Lv, Yuexi; Guo, Chunyan; Xu, Yingqiang; Niu, Zhichuan
Abstract: 320 × 256 mid-infrared focal plane arrays, together with linear arrays and single element devices, were fabricated based on type-II InAs/GaSb superlattice. At 77 K, the diode shows 50% cut-off wavelength of 4.8 μm and peak quantum efficiency of 38% at 3.7 μm without any bias dependence. The dominant dark current mechanisms at different temperatures are identified by R0 A analysis. At 160 K, R0 A of 2.2 × 10 3 Ω cm 2 and specific detectivity of 1.8 × 10 11 cm Hz 0.5 /W are demonstrated. Infrared imaging with an integration time of 5 ms demonstrates noise equivalent temperature difference of 12.3 mK and 34.2 mK, separately at 90 K and 120 K. Highlights: 320 × 256 high operating temperature mid-infrared FPA was fabricated in passivation by anodic sulfide. The dominant dark current mechanisms are identified by R0 A analysis at temperatures ranging from 10 K to 300 K. The diode shows 50% cut-off wavelength of 4.8 μm and peak quantum efficiency of 38% at 3.7 μm. The NETDs present mean values of 12.3 mK and 34.2 mK, separately at 90 K and 120 K.